Short Communication: The type and sound diversity of Kukuak Balenggek chicken (Gallus gallus domesticus) reared in West Sumatra, Indonesia - firda arlina; RUSFIDRA; DICKY ANDRIANO; CECE SUMATRI (Society for Indonesian Biodiversity, 2020)
Abstract. Arlina F, Rusfidra, Andriano D, Sumatri C. 2020. Short Communication: The type and sound diversity of Kukuak Balenggek chicken (Gallus gallus domesticus) reared by the association of Kukuak Balenggek Chicken Lovers in West Sumatra. Biodiversitas 21: 1914-1919. Kukuak Balenggek is one of the rare indigenous chicken in Indonesia. The number of population and genetic quality of Kukuak Balenggek Chicken (KBC) in in-situ has been decreasing from year to year. This encourages Kukuak Balenggek chicken lovers to found an association, namely Kukuak Balenggek Chicken Lovers, in order to conserve the germplasm native to West Sumatra. This study aimed to identify the type dan the song diversity of Kukuak Balenggek Chicken. A total of 180 adult males of Kukuak Balenggek chicken used in this study came from 32 members of the Association of Kukuak Balenggek Chicken Lovers. The survey method used in this research was purposive sampling. The analysis of data was carried out by descriptive statistical analysis. The parameters observed were the type of sound, number of crowing, number of crowing syllables, and duration of crow. The analysis of Kukuak Balenggek sound used the Cool Record Edit Pro computer software. The result showed that the percentage of sound type of Rantak Gumarang, Sigegek Angin, Alang Babega, Riak Ilia Aia, Ginyang, Ginyang Mataci, Gayuang Luluah were 37.78%, 26.67 %, 7.78%, 13.33%, 3.33%, 5.56%, and 5,56%, respectively. The highest of average, the number of crowing and syllable crowing based on the type of KBC sound was Sigegek Angin sound with an average of 9.48 crowing and 12.48 crowing syllable. While the longest average of Kukuak Balenggek chicken crowing duration was the Gayuang Luluah sound type with an average of 3.33 seconds.